2020
DOI: 10.3390/ijms21062131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Salt Stress on Growth of Spermosphere Bacterial Communities in Different Peanut (Arachis hypogaea L.) Cultivars

Abstract: Background: Exposure of seeds to high salinity can cause reduced germination and poor seedling establishment. Improving the salt tolerance of peanut (Arachis hypogaea L.) seeds during germination is an important breeding goal of the peanut industry. Bacterial communities in the spermosphere soils may be of special importance to seed germination under salt stress, whereas extant results in oilseed crop peanut are scarce. Methods: Here, bacterial communities colonizing peanut seeds with salt stress were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…The taxonomic profiling results demonstrated that the rhizosphere microbiota of the two grapevine varieties shared the same 10 dominant phyla ( Figure 1D ). All of the identified phyla have been previously reported and are known to predominate grapevine rhizospheres ( Zhang et al, 2019 ), as well as in those of peanut ( Xu et al, 2020 ), pomegranate ( Ravinath et al, 2022 ), barley ( Bulgarelli et al, 2015 ), and Arabidopsis thaliana ( Kielak et al, 2016 ). Nevertheless, the relative abundances of these phyla were distinct between 101-14 and 5BB ( Figures 1E , F ; Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomic profiling results demonstrated that the rhizosphere microbiota of the two grapevine varieties shared the same 10 dominant phyla ( Figure 1D ). All of the identified phyla have been previously reported and are known to predominate grapevine rhizospheres ( Zhang et al, 2019 ), as well as in those of peanut ( Xu et al, 2020 ), pomegranate ( Ravinath et al, 2022 ), barley ( Bulgarelli et al, 2015 ), and Arabidopsis thaliana ( Kielak et al, 2016 ). Nevertheless, the relative abundances of these phyla were distinct between 101-14 and 5BB ( Figures 1E , F ; Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an important oil crop and protein source, peanut plants can be grown in poor-quality soil [ 45 , 46 ], but their yield is significantly restricted by BW caused by R. solanacearum [ 27 ]. However, studies on the mechanisms of the peanut- R. solanacearum interaction are rare, and no R genes conferring resistance to BW have been identified in peanut.…”
Section: Discussionmentioning
confidence: 99%
“…The soil organic carbon was measured by humid oxidation with potassium dichromate (K 2 Cr 2 O 7 ), available nitrogen was extracted by using the alkaline hydrolysis diffusion method, and available phosphorus was determined by sodium bicarbonate (NaHCO 3 ) spectrophotometry [ 7 ]. Soil enzyme activities including invertase, urease, and neutral phosphatase were measured according to the previous study [ 3 ]. Soil invertase activity was determined using the 3, 5-dinitrosalicylic acid colorimetric spectrophotometry (absorbance at 508 nm); whereas urease activity was determined using sodium phenolate and sodium hypochlorite spectrophotometry (absorbance at 578 nm); soil neutral phosphatase activity was examined by using Solarbio Soil Neutral Phosphatase (S-NP) Activity Assay Kit (BC0465) [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Soil enzyme activities including invertase, urease, and neutral phosphatase were measured according to the previous study [ 3 ]. Soil invertase activity was determined using the 3, 5-dinitrosalicylic acid colorimetric spectrophotometry (absorbance at 508 nm); whereas urease activity was determined using sodium phenolate and sodium hypochlorite spectrophotometry (absorbance at 578 nm); soil neutral phosphatase activity was examined by using Solarbio Soil Neutral Phosphatase (S-NP) Activity Assay Kit (BC0465) [ 3 ].…”
Section: Methodsmentioning
confidence: 99%